An Algebraic Characterization of Affine Manifolds with G-Structure Satisfying a Homogeneity Condition (2010)
ABSTRACT: We give an algebraic characterization of the possible characteristictensors of an infinitesimally homogeneous affine manifold withG-structure.Such concepts were introduced in [5]